Pengaruh Risk Based Bank Rating terhadap Financial Distress dengan Bankometer Model Pada Busn Non Devisa - Rista Pristianti; Musdholifah Musdholifah (Jurnal Ilmu Manajemen, 2020)
Banks need to conduct evaluation activities to find out the current situation of the bank so that the health of the bank is not disturbed. Banking health is very important to be maintained because banks play an important role in society, especially as increasing the country's economic growth. This study aims to examine the effect of risk based bank rating on financial distress. The risk-based bank rating ratio consists of risk profiles that are proxied by NPL and LDR, good corporate governance which is proxied by the size of the board of directors and independent commissioners, earnings proxied by ROA, ROE, BOPO, and NIM, and capital proxied by CAR. The yardstick used in this research is the bankometer model. The research year is 6 years from 2013-2018. The population used in this study were all non-foreign exchange bank, amounting to 30. The sample was determined using purposive sampling so that 20 non-foreign exchange bank were found with data analysis techniques using logistic regression. Research data search using SPSS 25. The results of the study found the influence of LDR, the size of the board of directors, NIM, and CAR. LDR ratio has a significant negatif effect, board size has a significant positive effect, NIM has a significant negatif effect, and CAR has a significant negatif effect on financial distress. This because that fourth variable had important thing on liquidity, independent oversight, interest income, and capital adequacy. Whereas NPL, independent commissioners, ROA, ROE, and BOPO do not affect financial distress. This because the value of each variable already appropriate with Bank Indonesia determination and it summed up that Non-Foreign Exchange Bank already apply it well. This shows that risk based bank rating can be a parameter of bank health.